The Social Aspects in Water Management of Semarang’s Drainage System (Case Study of Banger Polder and Water Board BPP Sima) - R.C.B. van Ham; Schuller ,; Rick Heikoop; Henny Pratiwi A; S. I. Wahyudi (International Conference on Coastal and Delta Areas, 2015)
The climate is changing, rainfall will increase, the sea level is rising and the river dischargeswill change more. Delta areas are faced with the increasing risk of flooding. A traditional solutionagainst flooding is the Dutch polder system. These polder areas in the Netherlands are for many yearsmanaged and maintained by water boards. The Dutch water board model has not been used much inother countries. At this moment it is not known what the social aspects of water management are,which are important in the implementation of a polder system and institute in another cultural contextoutside the Netherlands. For this research, the Banger Polder pilot Project in Semarang is used as acase study, where a polder is constructed and the first public organization for water management inIndonesia has been established. The new water board named BPP SIMA, is similar to the Dutch waterboard model and is responsible for creating and maintain of dry feet in the area. The water boardshould work with the stakeholders to know what the important aspects of the social side in watermanagement are.This research looked at the available knowledge by the selected stakeholders, the acceptance ofthe water fee and the main interest of the selected stakeholders in the Banger polder . The method thatis developed in this research gives insights of the social aspects in water management. The focus ofthis research is on the social dimension of water management. The developed method is the existingthree layer model of water governance in combination with a 360 degrees evaluation. The three layermodel is a method to analyze the risks and opportunities within the water management. The three layermodel consist of three layers, content layer, institutional layer and relational layer. This requiresdifferent information which are collected by existing literature, field visits, discussions, surveys andinterviews.In the survey results appears that not all local stakeholders are familiar with the project and BPPSIMA. This is because the communication with the existing hierarchical structure between RW/RTand inhabitants about the knowledge transfer of the project is lacking. According to existing literaturein this research, it is important that inhabitants feel involved and feel ownership of the project toincrease the acceptance of the water fee. They are the most important stakeholders and must feelinvolved with the water management. Inhabitants need knowledge about water problems to accept thepolicy and measures are implemented more efficient.Keywords: social aspects, water management